SEASONAL INCIDENCE OF MIRID BUG (Cyrtorhinus lividipennis REUTER), PREDATOR OF BROWN PLANT HOPPER IN RICE ECOSYSTEM - R. JAGADESHWAR and CH. DAMODAR RAJU, R. VIJAYA RAGHAVENDRA, K. VIJAYA LAKSHMI CHITRA SHANKER, S. MALATHI (The Journal of Research, PJTSAU, 2019)
Rice (Oryza sativa L.) is the staple food crop of more than half of the world’s population. Asia is the leader in rice production accounting for about 90 per cent of the world’s production. India is the second largest producer and consumer of rice in the world after China which accounts for 21 per cent of the world’s total rice production. In India, rice is grown in an area of 43.49 million hectares with an annual production of 111.01 million tonnes (India stat, 2017-18).